Planning Model of Optimal Parking Area Capacity - Robert Maršanić; Zdenka Zenzerović; Edna Mrnjavac (Promet (Zagreb), 2010)
The demand for parking services is not a constant one, but rather varies from minimum to maximum. The range between the maximum and minimum demands and the dynamics of changes are the basic factor influencing the required size of the parking area capacity and the respective financial effects. The objective of this paper is to demonstrate that the queuing theory can be implemented in defining the optimal number of serving places (ramps) and the required capacity (number of parking spaces) in controlled access parking areas and that the established model can serve in business decision-making in respect to planning and development of the parking area capacity. The presented model has been verified in the example of the “Delta” parking area in the City of Rijeka but this model is particularly valuable as it can be implemented in any controlled access parking areas, i.e., parking areas with toll-bars under current or any other changed future conditions. KEY WORDS: planning of parking area capacities, optimal parking area capacity, queuing theory, parking area as a queuing system